The Formal Zigzag of the shapes of the volumetric structures as an influential on their functional performance Towards a Zigzagging Verticality in the 21 st Century: التعرّج الشّكليّ لهيئات البنى الحجميّة كمؤثرٍ على أدائها الوظيفيّ نحو عمارةٍ شاقوليّةٍ متعرّجةٍ في القرن 21 - Zahraa Mohammad Jumaa Kattoua, Safwat Ibrahim Basha, Mohamad Atalla Chick Mohamad (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
The vertical masses with their boxy shapes dominated the cities in the world as one of the most important product that invested the outputs of the industrial revolution, spreading from Chicago to New York and from there to the whole world to the Arab cities. Functionalism is no longer the only reason for moving vertically in the volumetric masses, it has become by time a field for ​​​​competition for height, contrary to Earth’s gravity. Those architectural structures with boxy forms transformed into a space that relies on a lot of machines which are necessary to operate these stacked floors, whether for heating, air conditioning or even lighting, what made them a burden that drains energy in an era that calls for sustainability, and negatively reflected on the environmental functionality performance which related to lighting, solarization or shading, and natural ventelation. they also produced many negatives, such as social isolation, away from the nature, strangeness of scale and lack of Harmony with the context, which was also reflected on the formal performance. So, meeting the needs of users with the existence of these vertical masses in their current forms seems unfulfilled to the design requirements. As a reaction, these negatives constituted as catalysts that made the transformation and the reconsidering of the design of the shapes of the volumetric structures are inevitable, taking into account the visual aspect and the sky line, getting rid of monotony and boredom and allowing a better quality of life, especially with regard to housing. The research deals with those morphological variables that affected the functional performance of the building, and aims to monitor the variations of the transformation cases that have occurred on the shapes of the vertical boxy masses since the beginning of the current century, through the approach of the analytical method of projects which the zigzag cases depended on their variable and extracting the effect of zigzag stimuli on the transformation of the formation and the nature of the zigzag, and then linking them to extracting functional or formal performance indicators as required by the purpose by comparing all previous cases. The research concluded, that the result lies in a close study of the relationship of the form and the function by reconsidering the shapes of the envelope line of the vertical mass and its relationship with the sky line and the way it moves from the horizon to the vertical such as zigzag and gradient moving or zigzag in the composition to increase the receiving surfaces and to improve the environmental functional performance or even perforating the boxy envelope to create a corner apartment and to get a direct connection with nature. The final indicators show that despite the different method of the zigzag, the largest percentage of zigzag goal is related to the environmental aspect to raise the functional performance of the building. The research recommends strengthening the role of the duality (the form- the function) by linking the shape of the structure to the desired needs and non- repetition without studying the validity of the form used for the intended time and place.